Mendekonstruksi bias dalam kurikulum: Menuju pendidikan yang inklusif dan beragam - Minnataka, Zahwah Fazat (Maliki Interdisciplinary Journal, 2026)
The national curriculum often carries hidden biases that ignore sociogeographic diversity, particularly in the 3T (Frontier, Outermost, and Disadvantaged) regions. This article aims to explore the importance of deconstructing curriculum bias towards an inclusive education system. Using a literature review method, this study finds that the core of deconstruction is dismantling the rigid, uniform mindset that imposes big city standards on areas with limited infrastructure. The findings indicate that management unpreparedness and a lack of bureaucratic honesty in curriculum transition have fueled academic apathy among students. As a solution, the concept of adaptive curriculum management is proposed, which grants autonomy to regions to modify learning methods based on local potential without abandoning the core of national achievements. This reconstrutions is crucial for fostering a sense of ownership and equal rights for all children in the Indonesian education system.